What do connectionism and social psychology offer each other? - Smith, Eliot R. (Journal of Personality & Social Psychology, 1996)
Social psychologists can benefit from exploring connectionist or parallel distributed processing models of mental representation and process and also can contribute much to connectionist theory in return. Connectionist models involve many simple processing units that send activation signals over connections. At an abstract level, the models can be described as representing concepts (as distributed patterns of activation), operating like schemas to fill in typical values for input information, reconstructing memories based on accessible knowledge rather than retrieving static representations, using flexible and context-sensitive concepts, and computing by satisfying numerous constraints in parallel. This article reviews open questions regarding connectionist models and concludes that social psychological contributions to such topics as cognition–motivation interactions may be important for the development of integrative connectionist models. Reprinted by permission of the publisher.